Effects of interactions between anthropogenic stressors and recurring perturbations on ecosystem resilience and collapse. Issue 1 (21st November 2022) - Keith, David A.; Benson, Doug H.; Baird, Ian R. C.; Watts, Laura; Simpson, Christopher C.; Krogh, Martin; Gorissen, Sarsha; Ferrer‐Paris, Jose R.; Mason, Tanya J.
Abstract: Insights into declines in ecosystem resilience and their causes and effects can inform preemptive action to avoid ecosystem collapse and loss of biodiversity, ecosystem services, and human well‐being. Empirical studies of ecosystem collapse are rare and hampered by ecosystem complexity, nonlinear and lagged responses, and interactions across scales. We investigated how an anthropogenic stressor could diminish ecosystem resilience to a recurring perturbation by altering a critical ecosystem driver. We studied groundwater‐dependent, peat‐accumulating, fire‐prone wetlands known as upland swamps in southeastern Australia. We hypothesized that underground mining (stressor) reduces resilience of these wetlands to landscape fires (perturbation) by diminishing groundwater, a key ecosystem driver. We monitored soil moisture as an indicator of ecosystem resilience during and after underground mining. After landscape fire, we compared responses of multiple state variables representing ecosystem structure, composition, and function in swamps within the mining footprint with unmined reference swamps. Soil moisture declined without recovery in swamps with mine subsidence (i.e., undermined), but was maintained in reference swamps over 8 years (effect size 1.8). Relative to burned reference swamps, burned undermined swamps showed greater loss of peat via substrate combustion; reduced cover, height, and biomass of regenerating vegetation; reduced postfire plant species richness and abundance; altered plant species composition; increased mortality rates of woody plants; reduced postfire seedling recruitment; and extirpation of a hydrophilic animal. Undermined swamps therefore showed strong symptoms of postfire ecosystem collapse, whereas reference swamps regenerated vigorously. We found that an anthropogenic stressor diminished the resilience of an ecosystem to recurring perturbations, predisposing it to collapse. Avoidance of ecosystem collapse hinges on early diagnosis of mechanisms and preventative risk reduction. It may be possible to delay or ameliorate symptoms of collapse or to restore resilience, but the latter appears unlikely in our study system due to fundamental alteration of a critical ecosystem driver. Efectos de las interacciones entre los estresantes antropogénicos y las perturbaciones recurrentes sobre la resiliencia y el colapso de los ecosistemas Resumen: La comprensión de la declinación en la resiliencia de los ecosistemas y sus causas y efectos puede orientar las acciones preventivas para evitar el colapso ecosistémico y la pérdida de biodiversidad, servicios ambientales y bienestar humano. Los estudios empíricos del colapso ecosistémico son escasos y se enfrentan a obstáculos como la complejidad del ecosistema, respuestas rezagadas y no lineales e interacciones entre las escalas. Investigamos cómo un estresante antropogénico podría reducir la resiliencia del ecosistema a una perturbación recurrente mediante la alteración de un causante importante. Estudiamos los humedales dependientes de aguas subterráneas que acumulan turbas y son propicios a incendios conocidos como pantanos de tierras altas en el sureste de Australia. Nuestra hipótesis fue que la minería subterránea (estresante) reduce la resiliencia de estos humedales a incendios (perturbación) al disminuir el agua subterránea, un causante clave para el ecosistema. Monitoreamos la humedad del suelo como un indicador de la resiliencia del ecosistema durante y después de la minería subterránea. Después de los incendios, comparamos la respuesta de múltiples variables de estado que representaban la estructura, composición y función del ecosistema en los pantanos dentro de la huella minera con los pantanos referenciales sin minería. La humedad del suelo declinó sin recuperación en los pantanos con hundimientos mineros (es decir, socavones) pero se mantuvo en los pantanos referenciales durante ocho años (tamaño del efecto: 1.8). En relación a los pantanos referenciales incendiados, los pantanos con socavones e incendios mostraron una mayor pérdida de turba mediante la combustión del sustrato; reducción en la cobertura, altura y regeneración de biomasa de la vegetación; reducción en la riqueza y abundancia de especies vegetales post incendio; alteraciones en la composición de especies vegetales; incremento en la mortalidad de las plantas leñosas; reducción en el reclutamiento post incendio de plántulas; y la extirpación de un animal hidrofílico. Por lo tanto, los pantanos con socavones mostraron síntomas fuertes de un colapso ecosistémico post incendio, mientras que los pantanos referenciales se regeneraron vigorosamente. Descubrimos que los estresantes antropogénicos redujeron la resiliencia de un ecosistema a perturbaciones recurrentes, lo que lo predispone al colapso. La eliminación de este colapso depende de un diagnóstico temprano de mecanismos y reducción del riesgo preventivo. Puede ser posible retardar o mitigar los síntomas del colapso o restaurar la resiliencia, aunque lo último parece ser improbable en nuestro sistema de estudio debido a la alteración fundamental de un causante importante del ecosistema. 人为压力和反复扰动之间的相互作用对生态系统恢复力及崩溃的影响: 【摘要】 深入了解生态系统恢复力下降的情况及其原因和影响, 可以为避免生态系统崩溃、生物多样性丧失、生态系统服务丧失及人类福祉减少的抢先行动提供指导。然而, 对生态系统崩溃的实证研究非常少见, 并且受到生态系统复杂性、非线性和滞后响应以及跨尺度互作的阻碍。本研究分析了一种人为压力源如何通过改变一个关键的生态系统驱动因素, 来降低生态系统面对反复扰动的恢复力。本研究关注澳大利亚东南部一种依赖地下水、积累泥炭, 且易受火灾影响的湿地类型, 即高地沼泽。我们假设地下采矿(压力源)通过减少地下水这一关键的生态系统驱动因素, 降低了这些湿地对景观火灾(扰动)的恢复力。我们监测了土壤湿度, 以作为地下采矿期间和之后的生态系统恢复力指标。在发生景观火灾后, 我们比较了代表采矿范围内的沼泽地与未采矿的参考沼泽地中生态系统结构、组成和功能的多状态变量的响应情况。研究发现, 在有矿井塌陷(即被破坏)的沼泽地中, 土壤湿度下降且没有恢复, 但在参考沼泽地中, 土壤湿度却可以保持8年(效应量为1.8)。相比于参考沼泽地, 采矿的沼泽地在火灾后出现更多基质燃烧导致的泥炭减少;再生植被的覆盖度、高度和生物量减少;火灾后植物物种丰富度和丰度降低;植物物种组成改变;木本植物死亡率增加;火灾后幼苗补充减少;还有一种亲水动物发生灭绝。因此, 采矿的沼泽地明显表现出火灾后生态系统崩溃的症状, 而参考沼泽地则可以旺盛地再生。我们发现, 采矿这种人为压力削弱了生态系统对反复扰动的恢复力, 使其容易崩溃。避免生态系统崩溃依赖于对机制的早期诊断和预防性的风险控制。推迟或减轻生态系统崩溃的症状或恢复生态系统恢复力也许可行, 但在我们的研究系统中, 由于一个关键的生态系统驱动因素的根本改变, 后者似乎不太可能实现。【翻译: 胡怡思; 审校: 聂永刚】